The Formula Industry is a Powerful Influence on Breastfeeding. Issue 4 (July 2022) - Spatz, Diane L.
Abstract : A report issued by the World Health Organization and United Nations Children's Fund emphasizes the powerful influence of formula companies on breastfeeding including all of their targeted strategies. Our breastfeeding expert, Dr. Spatz, summarizes this important report and offers suggestions on what nurses can do to counter formula company actions to promote their products.